Inflation is always and everywhere … a conflict phenomenon: post-Keynesian inflation theory and energy price driven conflict inflation, distribution, demand and employment - Eckhard Hein (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This paper reviews the post-Keynesian theory of inflation against the background of the simultaneous rise in inflation and profit shares in the course of the COVID-19 recovery and the Russian war in Ukraine. It distinguishes between the Keynes, Kaldor, Robinson, and Marglin tradition, and the Kalecki, Rowthorn, and Dutt tradition. Two prototype models in the latter tradition - the Dutt, Blecker-Setterfield and Lavoie variant, and the Rowthorn and Hein-Stockhammer variant - are discussed. The paper applies the latter to elucidate recent inflation trends propelled by increasing imported energy prices and then rising mark-ups. The effects of inflation-targeting central bank interest policies versus a post-Keynesian alternative macroeconomic policy approach are evaluated. It is argued that from a post-Keynesian perspective inflation is always and everywhere a conflict phenomenon, with different potential triggers. Adequate policies should thus focus on moderating distribution conflict by incomes policies, complemented by central banks targeting low long-term real interest rates, functional finance fiscal policies and international coordination of inflation targets.
Keywords: E12; E25; E31; E61; 330; Conflict inflation; Imported energy inflation shock; Post-Keynesian models